Peningkatan Pengetahuan Pola Makan Pada Klien Hipertensi Melalui Edukasi Suportif - Rispawati, Baik Heni; Ernawati; Dewi Nursukma Purqoti; Istianah; Hapipah; Heny Marlina Riskawati; Maelina Ariyanti (Jurnal Pengabdian, 2025)
Hypertension is a person who is said to have hypertension if he has a systolic blood pressure of more than 140 mmHg and a diastolic blood pressure of more than 90 mmHg. In this service, the aim is to find out how the incidence of hypertension in the community in Lokok Are Village, North Lombok Regency, regarding maintaining a diet in hypertensive clients. Efforts that have been made by the Santong Health Center regarding diet education provide diet education to hypertensive clients, but until now, many people in Lokok Are Village still do not know about how to maintain a diet, especially clients who have hypertension. Elderly people who have hypertension who cannot control their eating patterns will result in further complications. The method used in this service is by identifying people who suffer from hypertension, then blood pressure checks are carried out and material is provided on diet education for hypertensive clients through supportive education. In this service, 226 hypertensive clients were found to have hypertension and were identified as 16 hypertensive client respondents, and after being given counseling on diet education for hypertensive clients through supportive education, the community understands how to control themselves so that their hypertension does not recur. With this community service activity, it is hoped that it can help the community to understand the importance of maintaining a good diet and can reduce the incidence of hypertension in Loko Are Village, North Lombok District.